2021
DOI: 10.15835/nbha49212303
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing antioxidant defense system of mung bean with a salicylic acid exogenous application to mitigate cadmium toxicity

Abstract: Cadmium (Cd) accumulation is an emerging environmental hazard and has detrimental effects on plant growth and development. Salicylic acid (SA) is a well-known plant growth regulator that can initiate various molecular pathways to ameliorate Cd toxicity. The experiment was executed to scrutinize the mediatory role of SA to accelerate the defensive mechanism of mung bean in response to Cd stress. Mung bean plants were exposed to 0, 5, 10 and 15 mg Cd kg-1 of soil. Exogenous application of SA 0, 10-6 and 10-3 M w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 60 publications
1
12
1
Order By: Relevance
“…In this study, 250 mg/L SA increased the POD activity of N. officinale under Cd-contaminated condition, and 150, 200, and 250 mg/L SA increased the CAT activity. These results are not completely consistent with the previous report on Cyphomandra betacea (Liu et al, 2022) but consistent with the observations in pea (Popova et al, 2009;Khan et al, 2021), indicating that SA has different impacts on the various plants' antioxidant system. On the other hand, SA inhibits the activity of key enzymes, including POD, polyphenol oxidase, and phenylalanine ammonia lyase, to slow down lignin synthesis, delaying senescence (Wu et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, 250 mg/L SA increased the POD activity of N. officinale under Cd-contaminated condition, and 150, 200, and 250 mg/L SA increased the CAT activity. These results are not completely consistent with the previous report on Cyphomandra betacea (Liu et al, 2022) but consistent with the observations in pea (Popova et al, 2009;Khan et al, 2021), indicating that SA has different impacts on the various plants' antioxidant system. On the other hand, SA inhibits the activity of key enzymes, including POD, polyphenol oxidase, and phenylalanine ammonia lyase, to slow down lignin synthesis, delaying senescence (Wu et al, 2006).…”
Section: Discussioncontrasting
confidence: 74%
“…For rice, SA treatment increased its antioxidant enzyme activity and decreased the H 2 O 2 content to enhance the resistance to Cd stress (Guo et al, 2007); this also decreases the rice Cd content (Majumdar et al, 2020;Pan et al, 2021). Various other studies have shown similar effects of SA on mung beans, kidney beans and tomatoes under Cd stress (Tissa et al, 2000;Khan et al, 2021). In addition, SA also has demonstrated the effects on hyperaccumulators.…”
Section: Introductionmentioning
confidence: 91%
“…Our results demonstrated that the application of N-P fertilizers under a low-W regime considerably reduced the ROS. This may be related to the enhancement of antioxidant enzyme activities (SOD, CAT, and POD) under N-P supply (Figures 2G-I), since N-P nutrition could improve the synthesis and physiological activities of antioxidant enzymes (Khan et al, 2021;Roy et al, 2021a,c). Therefore, the addition of N-P fertilizers under waterlimited environments can improve the plant water status, the osmolytes content, and the activity of antioxidant enzymes, favoring the ROS homeostasis (low production of H 2 O 2 and O •−…”
Section: Discussionmentioning
confidence: 97%
“…Drought can also induce the excessive generation of reactive oxygen species (ROS) in plants; and thereby results in oxidative stress ( Cruz de Carvalho, 2008 ). In addition, salinity and HMs stress are also considered among the environmental factors that limit crop yield in many countries ( Abd El-Mageed et al, 2018 ; Ye et al, 2019 ; Sofy et al, 2020 ; Taha et al, 2020 ; Dustgeer et al, 2021 ; Khan et al, 2021 ; Seleiman et al, 2022 ).…”
Section: Abiotic Stressmentioning
confidence: 99%